NEW SPECIES OF EXOCHONOTUS BARR, 1 9 8 0 (COLEOPTERA: CLERIDAE: ENOPLIINAE) AND A KEY FOR CHILEAN TAXA (Acta Entomológica Chilena, 2022)
Two new species of Exochonotus Barr, 1980, E. beechi n. sp. and E. bimaculatus n. sp., from north and central Chile, are described and a key is provided for all the known Chilean taxa.
Keywords: Coleóptera, Cleridae, Enopliinae, Exochonotus, new species, Chile